1989
DOI: 10.1212/wnl.39.3.349
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral changes associated with caudate lesions

Abstract: We report behavioral and cognitive characteristics of 12 patients with caudate nuclei lesions, 11 unilateral and one bilateral. These patients developed an acute behavioral change characterized by apathy, disinhibition, or a major affective disturbance. The pattern of personality change correlated with size and location of lesion within the caudate but not the laterality. Seven patients were further compared with matched controls on a series of neuropsychological tests. Their performance was impaired on tasks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
161
0
8

Year Published

1991
1991
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(181 citation statements)
references
References 3 publications
12
161
0
8
Order By: Relevance
“…In adults without primary psychiatric conditions, a positive relationship between executive function and caudate activity (Lombardi et al 1999;Volkow et al 1998) and volume (Fuh and Wang 1995;Mendez et al 1989) has been found. The present sample, however, included children prior to the age at which caudate volumes peak (Caviness et al 1996;Hardan et al 2003;McAlonan et al 2002;Thompson et al 2000).…”
Section: Caudate Volumes and Cognitive Performancementioning
confidence: 99%
See 1 more Smart Citation
“…In adults without primary psychiatric conditions, a positive relationship between executive function and caudate activity (Lombardi et al 1999;Volkow et al 1998) and volume (Fuh and Wang 1995;Mendez et al 1989) has been found. The present sample, however, included children prior to the age at which caudate volumes peak (Caviness et al 1996;Hardan et al 2003;McAlonan et al 2002;Thompson et al 2000).…”
Section: Caudate Volumes and Cognitive Performancementioning
confidence: 99%
“…Caudate nucleus lesions lead to impairments in planning and problem solving (Mendez et al 1989;Schmidtke et al 2002), mental flexibility (Lombardi et al 1999), learning (Poldrack et al 1999), attention (Mendez et al 1989), short-term and long-term memory (Fuh and Wang 1995), retrieval (Mendez et al 1989), and verbal fluency (Fuh and Wang 1995). Thus, the caudate may represent one underlying structural correlate of the cognitive deficits observed in ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from lesion studies in animals and humans suggests that the role of the basal ganglia in cognition may be conceived in terms of "network-specific" functions, whereby damage to different components in cortical-subcortical networks results in a similar functional deficit (e.g., Cummings, 1993;Divac et al, 1967;Mendez et al, 1989). The exact role of the nonmotor basal ganglia-thalamocortical circuits in higher level functions is not yet fully determined, but there is emerging evidence that several of these subcortical-cortical loops (i.e., anterior cingulate, dorsolateral prefrontal) may be involved in various cognitive processes which could influence language processing (Cummings, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The former clinical pictures are less well explained by neuronal degeneration in the striate body. It is argued that atrophy in the striate body disrupts the neuronal loop between prefrontal cortical regions and thalamic feedback [3,4,71,85,98,115]. Other investigators explain cognitive deficits by global cortical, subcortical, and white matter atrophy [28,79], selective laminar loss of a nonphosphorylated neurofilament (SMI-32 ir) bearing pyramidal cells [25], and reduced nerve cell density in layers V and VI of the prefrontal cortex [108,109].…”
Section: Introductionmentioning
confidence: 99%